Direct Access to Amides from Nitro‐Compounds via Aminocarbonylation and Amidation Reactions: A Minireview. Issue 12 (2nd September 2021) - Barak, Dinesh S.; Batra, Sanjay
Abstract: The ubiquity of the amide bond in functional molecules including proteins, natural products, pharmaceuticals, agrochemicals and materials provides impetus to design and develop newer strategies for the generation of this linkage. Owing to growing awareness about sustainability and development of benign strategies, the traditional route of synthesis of amides via reaction between carboxylic acids and amines in the presence of stoichiometric amount of coupling reagents is tagged to be harsh and wasteful. In one of the unconventional routes, nitro compounds are used directly as amine surrogates for preparing amides mostly via aminocarbonylation and amidation reactions. Typically, such processes involves nitroarenes owing to their propensity to transform into nitroso, hydroxylamine, diazo, hydrazine or aniline intermediates in situ under the influence of suitable catalyst or oxidant. This short review provides the comprehensive overview of these reactions including insight into the scope and their mechanisms. Abstract : The present review describes the synthesis of amides from nitro group containing aliphatic and aromatic compounds via aminocarbonylation and amidation reactions.